Clinical Outcomes of the Cochlear™ Nucleus® 5 Cochlear Implant System and SmartSound™ 2 Signal Processing - Runge, Christina L.; Henion, Kathryn; Tarima, Sergey; Beiter, Anne; Zwolan, Teresa A. (Journal of the American Academy of Audiology, 2016)
Background: While published data exist regarding cochlear implant (CI) outcomes from large academic programs, evidence of benefit based on national, multicenter clinical trials is needed for information regarding typical patient outcomes of devices implanted by U.S. centers representing larger academic to smaller hospital-based programs.Purpose: This nationwide trial evaluated outcomes in a group of newly implanted adult recipients of the Cochlear™ Nucleus® 5 CI system and SmartSound™ 2 signal processing. Unlike previous clinical trials, the AzBio sentence test was used and represents recent transition in our field to use of more challenging test materials. It was hypothesized that (1) speech perception scores in quiet with SmartSound™ 2 signal processing would not be statistically different from previous-generation devices; (2) speech perception scores in noise with SmartSound™ 2 signal processing would be better with enhanced microphone directionality; (3) speech perception scores in noise will be better with the preferred SmartSound™ 2 program for listening in noise; and (4) cochlear implantation would improve quality of life as assessed by the updated Health Utility Index Mark 3 (HUI3). A secondary purpose was to examine the relationships among the current and previously used speech perception tests of the Minimum Speech Test Battery (MSTB). It was hypothesized that speech perception scores within the same test interval would show predictive relationships.Research Design: Prospective, single-arm, repeated-measures study across 13 CI centers in the United States between February 2010 and June 2012. The participating centers ranged from larger academic to smaller hospital-based programs to accurately represent the diversity of programs in the United States.Study Sample: Participants were 38 postlingually deafened adult CI candidates.Data Collection and Analysis: Primary measures were Consonant-Nucleus-Consonant (CNC) words in quiet and the AzBio Sentence Test in Quiet (AzBioQ) and in Noise (AzBioN) tested at preoperative, and 3-, 6-, and 12-mo postactivation intervals. Quality of life was measured with the HUI3. For the secondary objective, statistical analyses were performed to investigate the predictive properties between current and previously used MSTB tests.Results: Mean CNC scores were significantly higher compared to the Nucleus® 24 Contour™ at 3 mo (p < 0.05) postactivation and showed no difference compared to the Nucleus® Freedom™ at 6 mo postactivation. Both SmartSound™ 2 FOCUS and NOISE programs provided significant improvements in performance in noise over the EVERYDAY program (p < 0.001), and performance with the FOCUS program was significantly better compared to the NOISE program (p < 0.001). Speech perception in noise was not related to patients’ subjective program preferences. Quality-of-life outcomes showed significant improvements from the preoperative to 6-mo postactivation interval (p < 0.05–0.001). Strong and significant correlations were found between preoperative CNC and AzBioQ and preoperative Hearing-in-Noise Test sentences in Quiet (HINTQ) and AzBioQ. At 12-mo postactivation, there were strong and highly significant correlations between CNC and AzBioQ, HINTQ and AzBioQ, and Hearing-in-Noise Test sentences in Noise and AzBioN (all p < 0.001).Conclusions: Results of this national clinical trial showed significant improvements in speech perception and quality of life following cochlear implantation. SmartSound™ 2 signal processing features showed a significant benefit of FOCUS when listening in noise, although preference of signal processing feature did not correlate with performance. Significant correlations were observed between speech perception tests. The findings of this study can be applied in clinical assessment, programming, and follow-up for CI candidates and recipients.
Keywords: cochlear implant; Minimum Speech Test Battery; nucleus; program preference; quality of life; SmartSound™ 2; speech perception